Textiles for hygiene and infection control - McCarthy, B. J. (Woodhead Publishing, 2011)
Understanding and improving hygiene and healthcare products is essential for improving infection prevention. Continuing Woodhead Publishing's series of specialised medical textile books, Textiles for hygiene and infection control provides readers with the latest developments in healthcare materials for hygiene and infection applications. Part one offers an insight into design and production techniques for hygiene textiles. Chapters discuss nanotechnology and it's applications in hygiene textiles, knitted spacer fabrics, innovative and sustainable packaging and biodegradable hygiene products. Part two explores design and production techniques for infection control textiles. Chapters examine micro-organisms, infection and the role of textiles, the creation of barrier textiles through plasma processing and methods for ensuring fabrics survive sterilisation. Part three concludes by investigating the variety of available hygiene and infection control products. Chapters consider washable textile-based absorbent products for incontinence, coated textiles for skin infections and antimicrobial treatments of textiles for hygiene and infection control applications from an industrial perspective. Textiles for hygiene and infection control is an essential reference for manufacturers, designers, engineers and producers of hygiene and infection control products. It is also a useful tool for medical scientists, surgeons and nurses. Offers insight into design and production techniques for hygiene textilesChapters discuss a range of applications, such as the use of textiles for incontinenceAn essential reference for manufacturers, designers, engineers and producers of hygiene and infection control products.
"The Textile Institute."
Keywords: Textile fabrics -- Health aspects.; Infection -- Prevention.; Biomedical materials.; elektronické knihy; electronic books